Uso de lidocaína e bupivacaína na anestesia espinhal de cágado -de-barbicha Phrynops geoffroanus (Schweiger, 1812) - Ribeiro, Priscilla Inocêncio Rodrigues (2011)
The objective was to evaluate the efficacy of lidocaine and bupivacaine in spinal turtles by species Phrynops geoffroanus to promote sensory and motor block in the regions of the tail, vent and later members. Ten females with average weight of 2.14 kilograms (kg) were submitted to two anesthetic protocols, with an interval of 10 days: 4.6 milligrams (mg) / kg of lidocaine 2% and 1.15 mg / kg of bupivacaine 0.5% deposited in the spinal region of space proximal intercoccígeo. The anesthetic action in the tail for the two anesthetics was instantaneous, that is less than 1 min. Regarding the latency period in later members (PM), we obtained 4.5 ± 4.37 min and instant messaging as their average values for lidocaine and bupivacaine. The presence of maximum muscle relaxation and analgesia was 34.50 ± 33.28 min and 114.55 ± 39.89 min in the tail / vent to 2% lidocaine. and bupivacaine 0.5%, respectively. Medium corresponding to 24 ± 23.42 min and 110.50 ± 28.81 min was obtained by the later members use of anesthetics in the same sequence. The recovery period, equivalent to the time required to return to preanesthetic parameters from the start scoring 2 for muscle relaxation, was 37.00 ± 23.63 min for lidocaine and 61.5 ± 36.59 min for bupivacaine. Times skillful anesthesia achieved with the use of both anesthetic protocols are sufficient to perform simple surgical procedures and routine, such as amputation of the penis and suturing of skin lacerations. The choice of anesthetic to be applied will depend on the average time the procedure was performed to average 2% lidocaine and bupivacaine half-hour average of one hour.